Identification of enteroendocrine cells of Tropidurus torquatus and Salvator merianae (Squamata: Lacertilia) - Barbosa Lopes, Fernanda (2021)
The Squamata lizards Tropiduros torquatus and Salvator merianae are omnivores with different diets and foraging strategies, which requires adequate physiological responses of enteroendocrine cells, since they control digestive events, gastrointestinal epithelium renewal, metabolism and food intake. Thus, we aim to describe the distribution and frequency of enteroendocrine cells in the digestive tract of these two lizard’s species. Five individuals of each species were collected, euthanized and the digestive organs removed. Histological sections were submitted to the techniques of Grimelius for argyrophilic cells and Masson-Fontana for argentaffin cells. Both endocrine cells were found in the lining and glandular epithelium, with a pyramidal, oval, rounded, or elongated shape. Argyrophilic cells were observed in both species, predominantly in the stomach, but absent in the cranial esophagus. Argentaffin cells were distributed in almost the entire digestive tract but absent in the cranial portion of the esophagus and small intestine in both species, and with high frequency in the T. torquatus pyloric region. The absence of argentaffin cells in the cranial portion of the small intestine is intriguing and may reveal greater neural control over certain secretomotor functions involving this segment. We concluded that the inter-specific and inter-regional variations in the distribution and frequency of these cells may reflect the regulatory functions and mechanisms of each organ, taking also into account the oscillations of the food and nutritional status of animals in the wild.